(untitled) (Praxis Educativa, 2022)
We present a systematization of practices carried out as a team for initial teacher training in Biology and Physics. This systematization focuses on analyzing the ways in which we accompany teacher residents. Positioned in Popular Education, we aim at the training of reflective professionals, who can have a critical view of both, their context and their practice. We performed an analysis based on our records around the accompaniments carried out, characterizing the devices and strategies deployed. Among the latter we highlight: the establishment of limits; the valorization of practical knowledge; the reinforcement of self-esteem; the problematization and orientation of aspects to be improved through questions, suggestions, comments, specific bibliography; the interpellation in relation to pedagogical intentions, expectations and purposes of education; the internal coherence of the proposals and of these with practice. This systematization allowed us to strengthen some certainties in our praxis, as well as to learn from our own practice and to rethink the accompaniment in the future.